Acute respiratory infections in the children of the Southern states of India, with a special focus on the newly carved states - Challa, Sairam; Gangam, Sukhdas; Amirapu, Pallavi (International Journal of Contemporary Pediatrics, 2017)
Background: Southeast Asia stands first in number for ARI incidence, accounting for more than 80% of all incidences together with sub-Saharan African countries. In India, more than 4 lakh deaths every year are due to pneumonia. In June 2014, state of Andhra Pradesh has been divided into two new states of Telangana and Andhra Pradesh. Both the new states will face the challenges of new born states in the coming years. India’s progress on the MDGs (Millennium Development Goals) for 2015 requires that the new states overcome the challenges effectively. An attempt is made to analyze the available data in the field of ARI Control which can serve as a baseline to monitor the progress in field in the newly carved sates. Objectives: To study the awareness and treatment seeking behaviour of mothers on ARI in children of the Southern states of India with a special focus on the newly carved states. Methods: Secondary data published in the district level household and facility survey-4 is analyzed. Results: Awareness about danger signs of ARI was better in Kerala followed by Telangana and Andhra Pradesh. Mothers in Tamil Nadu seek government facilities more often than those of other states for ARI management. Conclusions: Early diagnosis and treatment is the corner stone for controlling Under-5 mortality attributable to ARI. Kerala sets an example for the rest of the southern states by its higher awareness levels and better treatment seeking behaviour following an episode of ARI. Background: Southeast Asia stands first in number for ARI incidence, accounting for more than 80% of all incidences together with sub-Saharan African countries. In India, more than 4 lakh deaths every year are due to pneumonia. In June 2014, state of Andhra Pradesh has been divided into two new states of Telangana and Andhra Pradesh. Both the new states will face the challenges of new born states in the coming years. India’s progress on the MDGs (Millennium Development Goals) for 2015 requires that the new states overcome the challenges effectively. An attempt is made to analyze the available data in the field of ARI Control which can serve as a baseline to monitor the progress in field in the newly carved sates. Objectives: To study the awareness and treatment seeking behaviour of mothers on ARI in children of the Southern states of India with a special focus on the newly carved states.Methods: Secondary data published in the district level household and facility survey-4 is analyzed.Results: Awareness about danger signs of ARI was better in Kerala followed by Telangana and Andhra Pradesh. Mothers in Tamil Nadu seek government facilities more often than those of other states for ARI management.Conclusions: Early diagnosis and treatment is the corner stone for controlling Under-5 mortality attributable to ARI. Kerala sets an example for the rest of the southern states by its higher awareness levels and better treatment seeking behaviour following an episode of ARI.